Comparative analysis of the proprietary navigation system and the built-in Unity engine tool - Kempny, Maciej; Barszcz, Marcin (Journal of Computer Sciences Institute, 2021)
Navigation systems are advanced tools that allow you to create characters intelligently moving around the game world. The purpose of this thesis was to conduct a comparative analysis of the proprietary navigation system “AlchemyNavigation” and the built-in tool of the Unity engine - “NavMesh”. An proprietary application created with the Unity engine was used to conduct the research, under which identical scenarios based on the tested systems were implemented. Finally, on the basis of the collected results and documentation of the research objects, a comparative analysis was carried out and proved the thesis that own solutions can match the default solutions.